2017
DOI: 10.3747/co.24.3632
|View full text |Cite
|
Sign up to set email alerts
|

Survivorship Care Plans for Breast Cancer Patients: Understanding the Quality of the Available Evidence

Abstract: AimThe overall goal of the present study was to contribute to consistency in the provincial approach to survivorship care planning through knowledge synthesis and exchange. Our review focused on the research concerning the physical and emotional challenges of breast cancer (bca) patients and survivors and the effects of the interventions that have been used for lessening those challenges. MethodsThe psychosocial topics identified in bca survivorship care plans created by two different initiatives in our provin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 81 publications
0
7
0
1
Order By: Relevance
“…Burke et al 6 used focus groups to demonstrate the need for patient education regarding the transition between active cancer treatment and survivorship. Nonetheless, an umbrella meta-analysis conducted by D'Souza et al 7 revealed the paucity of actual data regarding best practices in survivorship care planning.…”
Section: Discussionmentioning
confidence: 99%
“…Burke et al 6 used focus groups to demonstrate the need for patient education regarding the transition between active cancer treatment and survivorship. Nonetheless, an umbrella meta-analysis conducted by D'Souza et al 7 revealed the paucity of actual data regarding best practices in survivorship care planning.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive behavioral therapy (CBT) is a structured psychological approach to solving current problems, modifying behavior and useless thinking, promoting a reduction in symptoms of anxiety and depression, improving social life, and finding benefits in the cancer experience, with unquestionable improvement in quality of life 19,20 .…”
Section: Stressmentioning
confidence: 99%
“…Evaluating the complex interaction between diet and physical activity and better BC outcomes resulted in a significant reduction in BC incidence and enhanced survival rates ( 14 , 15 ). Substantial evidence underlines the importance of a balanced diet and increased physical activity to prevent BC and reduce the chances of recurrence and mortality in both pre- and post-menopausal women ( 16 , 17 ). Currently, exercise and nutrition are considered as two integrative therapy components that play a crucial role in relieving the side effects of active cancer treatment and especially cancer-related fatigue ( 18 ).…”
Section: Introductionmentioning
confidence: 99%